Hierarchical pore MnFe2O4 catalyst for catalytically degrading methyl mercaptan at normal temperature as well as preparation method and application of hierarchical pore MnFe2O4 catalyst

Through the use of multi-stage pore MnFe2O4 catalyst, the problem of poor stability of existing catalysts at room temperature is solved, and the efficient and stable degradation of methylmercaptan is achieved, and it has important industrial application prospects.

CN119455973APending Publication Date: 2025-02-18KUNMING UNIV OF SCI & TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411587255.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The existing catalysts have high active temperature and poor stability during the catalytic degradation of methylmercaptan, and are difficult to efficiently and stably degrade methylmercaptan in the catalytic degradation of methylmercaptan, especially under normal temperature and high aerial speed conditions.

Method used

A multi-stage porous MnFe2O4 catalyst is used, which is formed by high-temperature calcining iron source, manganese source and template agent, has a high specific surface area and rich active sites, and can efficiently degrade methylene mercaptan at room temperature.

Benefits of technology

It achieves efficient and stable degradation of methylmercaptan at room temperature, with a degradation rate of 100%, and can maintain a 100% degradation efficiency after 400 hours, significantly improving the stability and regeneration of the catalyst.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119455973A_ABST
    Figure CN119455973A_ABST
Patent Text Reader

Abstract

The invention discloses a hierarchical porous MnFe2O4 catalyst for catalytically degrading methyl mercaptan at normal temperature as well as a preparation method and application of the hierarchical porous MnFe2O4 catalyst, and belongs to the technical field of organic sulfur pollutant treatment. The hierarchical porous MnFe2O4 catalyst is obtained by grinding, mixing and calcining an iron source, a manganese source and a template agent. The hierarchical porous MnFe2O4 catalyst disclosed by the invention is simple and convenient in synthesis process, low in cost and suitable for large-scale production, and has great industrial practicability; meanwhile, the catalyst can be used for completely converting methyl mercaptan at the room temperature of 30 DEG C, and the temperature of 300-400 DEG C required by other reported catalysts is far lower than that of 300-400 DEG C required by other reported catalysts; at normal temperature and normal pressure, the catalyst can still achieve 100% complete conversion of methyl mercaptan after being used for 400 hours; the regenerated catalyst has the same service life as the original catalyst; the catalyst has the characteristics of high activity, high stability and good reproducibility.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of organic sulfur pollutant treatment, and more specifically relates to a multi-level porous MnFe2O4 catalyst for catalytic degradation of methyl mercaptan at room temperature, and a preparation method and application thereof. Background Art

[0002] Methyl mercaptan, as a typical sulfur-containing volatile organic compounds (VOCs), easily accumulates in the air to form organic aerosols, which in turn cause serious air pollution problems such as atmospheric photochemical smog and haze. Methyl mercaptan is widely present in petroleum processing, natural gas, coke ovens, tanneries, paper mills, and various pollution control facilities (such as wastewater treatment systems and sanitary landfill systems), and its emissions pose a potential threat to the environment and human health. Because methyl mercaptan is highly toxic and corrosive, and has an extremely low olfactory threshold (only 0.04ppb / v), it can cause strong discomfort even at extremely low concentrations; long-term exposure to high-concentration methyl mercaptan environments may cause serious respiratory problems and even respiratory paralysis. In addition, methyl mercaptan will accelerate the corrosion of metal pipes and equipment, increase maintenance costs, and may cause safety hazards. According to the National Standard of the People's Republic of China "Emission Standards for Odor Pollutants" (GB-14554-93), the emission requirements for methyl mercaptan are very strict, among which the first-level emission standard for the organic sulfur species methyl mercaptan at the factory boundary (0.004mg / m 3 ) than inorganic sulfur species H2S (0.03mg / m 3 ) is one order of magnitude lower. Therefore, basic research on methyl mercaptan treatment technology is of great significance for improving the quality of the atmospheric environment, protecting people's physical and mental health, and achieving the national sulfur emission reduction goals.

[0003] At present, the methods for removing methyl mercaptan mainly include adsorption, alkaline solution absorption, combustion, biological method and catalytic degradation. Although the adsorption method can effectively remove low concentrations of harmful gases, it has limited adsorbent capacity, complex regeneration process, and secondary pollution. The alkaline solution absorption method has a long contact reaction time and incomplete gas-liquid contact, resulting in low removal efficiency. Although the direct combustion method has high purification efficiency, it requires a higher combustion temperature and consumes more energy. The microbial method has a long treatment cycle and is difficult to achieve large-scale industrial application. In contrast, the catalytic degradation method is characterized by high efficiency, no additives, and avoidance of SO x The characteristics of secondary pollutant generation have become a key research focus at home and abroad.

[0004] The commonly used methyl mercaptan catalytic degradation technology currently relies mainly on a series of catalysts, such as cerium-based catalysts, HZSM-5 molecular sieve catalysts, and molybdenum-based catalysts. Although these catalysts improve their catalytic activity by improving their acidity and alkalinity and redox properties, under carbon-containing and sulfur-containing atmosphere conditions, the catalysts are susceptible to poisoning by sulfur species and are prone to sulfur and carbon accumulation, resulting in decreased catalyst activity and rapid deactivation (for example, HZSM-5 molecular sieves begin to deactivate after 6 hours of reaction; the life span of nano CeO2 catalytic degradation of methyl mercaptan is only 10 hours). In addition, these catalysts usually need to be at a higher temperature (≥400°C) to exert the best catalytic performance, and it is difficult to achieve efficient and stable catalytic degradation of methyl mercaptan under harsh conditions of normal temperature and high air velocity. Therefore, it is of great significance to develop catalysts that can work efficiently and stably under harsh conditions of normal temperature and high air velocity. The common problems of existing catalysts in the catalytic degradation of methyl mercaptan are high active temperature and poor stability. Especially under normal temperature and high air velocity conditions, catalysts that can efficiently and stably degrade methyl mercaptan are still relatively rare. Summary of the invention

[0005] The purpose of the present invention is to provide a multi-level porous MnFe2O4 catalyst for catalytic degradation of methyl mercaptan at room temperature and a preparation method and application thereof, so as to solve the problems of high active temperature and poor stability of existing catalysts in the catalytic degradation process of methyl mercaptan.

[0006] To achieve the above object, the present invention provides the following solutions:

[0007] One of the technical solutions of the present invention is to provide a method for preparing a multi-level porous MnFe2O4 catalyst for catalytic degradation of methyl mercaptan at room temperature, comprising the following steps:

[0008] The iron source, the manganese source and the template are ground and mixed to obtain a mixture; the mixture is calcined to obtain the multi-level porous MnFe2O4 catalyst.

[0009] The preparation principle of the multi-level porous MnFe2O4 catalyst of the present invention is to form a multi-level porous structure by calcining a uniform mixture of an iron source, a manganese source and a template at high temperature, and utilizing the gas (such as CO2 and water vapor) generated by the decomposition of the template at high temperature. In this process, metal ions undergo redox reactions at high temperatures to form MnFe2O4 crystals, while the decomposition of the template and the escape of gas leave a large number of pores in the material, thereby forming a multi-level porous structure catalyst with a high specific surface area and abundant active sites.

[0010] The mechanism that the multi-level pore MnFe2O4 catalyst of the present invention can efficiently degrade methyl mercaptan at room temperature is mainly reflected in two aspects: first, the multi-level pore structure increases the active sites of the catalyst, and these active sites can effectively adsorb and activate methyl mercaptan molecules. At room temperature, the active sites on the surface of the MnFe2O4 catalyst can promote the decomposition of methyl mercaptan by forming chemical bonds or physical adsorption with methyl mercaptan molecules; secondly, the MnFe2O4 catalyst with a multi-level pore structure has a higher specific surface area, which increases the mass transfer rate of methyl mercaptan molecules while increasing the active sites on the catalyst surface, and improves the utilization rate of existing active sites. The hierarchical pore structure also improves the catalyst's carbon and sulfur capacity, and improves the activity and stability of methyl mercaptan degradation.

[0011] Preferably, the iron source includes one or more of ferric nitrate, ferric chloride and ferric acetate; the manganese source includes one or more of manganese nitrate, manganese chloride, manganese acetate and potassium permanganate.

[0012] Preferably, the template comprises citric acid and / or oxalic acid;

[0013] When citric acid and oxalic acid are used as templates to prepare hierarchical porous MnFe2O4 catalysts, the gases generated by their decomposition at high temperatures effectively form a hierarchical pore structure, increasing the specific surface area and active sites of the catalyst. These templates not only regulate the morphology and pore size distribution of the catalyst, but also have good dispersibility and environmental protection, ensuring the high activity and stability of the catalyst. Compared with other templates, citric acid and oxalic acid are easy to use, low cost and non-toxic, making them ideal choices for preparing high-performance catalysts.

[0014] Preferably, the molar ratio of the iron source, the manganese source and the template is 1-3:1:1-10.

[0015] Preferably, the grinding and mixing time is 10 to 60 minutes.

[0016] Preferably, the calcination is carried out in an air atmosphere, the calcination temperature is 300-500°C, the calcination heating rate is 2-10°C, and the calcination holding time is 2-4h;

[0017] The calcination temperature and time can ensure the best morphology, catalytic activity and stability of the multi-level porous MnFe2O4 catalyst. These conditions allow the template to fully decompose, form a multi-level porous structure, increase the specific surface area and active sites, and at the same time be sufficient to allow the metal ions (Fe 3+ and Mn 2+) to undergo redox reaction to ensure the integrity and purity of the MnFe2O4 crystals. Beyond this range, too low temperature and too short time will lead to unsatisfactory morphology and incomplete crystallization, while too high temperature and too long time will destroy the pore structure and cause excessive crystal growth, thereby reducing the activity and stability of the catalyst.

[0018] The second technical solution of the present invention: provides a multi-level porous MnFe2O4 catalyst prepared by the preparation method of the multi-level porous MnFe2O4 catalyst for catalytic degradation of methyl mercaptan at room temperature.

[0019] The multi-level porous MnFe2O4 catalyst of the present invention comprises multi-level pores such as micropores, mesopores and macropores, has a sponge-like pore structure, is suitable for catalytic degradation of sulfur-containing volatile organic compound methyl mercaptan gas at room temperature, exhibits relatively excellent activity and stability, and has practical application prospects.

[0020] The third technical solution of the present invention is to provide the application of the multi-level porous MnFe2O4 catalyst in the catalytic degradation of methyl mercaptan at room temperature.

[0021] Technical solution 4 of the present invention: Provide a method for catalytic degradation of methyl mercaptan at room temperature using the multi-level porous MnFe2O4 catalyst, comprising the following steps:

[0022] The multi-level porous MnFe2O4 catalyst is loaded into the reactor, and methyl mercaptan is introduced into the reactor to perform catalytic degradation of methyl mercaptan.

[0023] Preferably, the particle size of the multi-level porous MnFe2O4 catalyst is 40-60 mesh, the loading amount of the multi-level porous MnFe2O4 catalyst is 0.04-0.2 g; the concentration of methyl mercaptan is 1-5000 ppm, and the space velocity of methyl mercaptan is 10-200000 h -1 ; The pressure of the catalytic degradation is normal pressure, and the temperature of the catalytic degradation is normal temperature.

[0024] The multi-level porous MnFe2O4 catalyst of the present invention can achieve 100% degradation of methyl mercaptan at normal temperature, normal pressure and high gas space velocity, and can still achieve 100% degradation of methyl mercaptan after the degradation process lasts for 400 hours.

[0025] The present invention discloses the following technical effects:

[0026] 1. The multi-level porous MnFe2O4 catalyst of the present invention has a simple synthesis process, low cost and is suitable for large-scale production, and has great industrial applicability.

[0027] 2. The multi-level porous MnFe2O4 catalyst prepared by the present invention has the following advantages compared with the existing catalysts for degrading methyl mercaptan:

[0028] (1) High activity. Compared with the cerium-based catalysts, HZSM-5 molecular sieve catalysts and molybdenum-based catalysts reported in the literature, this catalyst can achieve complete conversion of methyl mercaptan at room temperature of 30°C, which is much lower than the 300-400°C required by other reported catalysts;

[0029] (2) Long-term stability. At room temperature and pressure, the catalyst can still achieve 100% complete conversion of methyl mercaptan within 400 hours, which is much higher than the stability of other catalysts reported in the literature;

[0030] (3) Good regeneration. The regenerated catalyst has the same service life as the original catalyst, and its performance and structure have hardly changed after multiple regenerations. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 This is a SEM image of the multi-level porous MnFe2O4 catalyst obtained in Example 1;

[0032] Figure 2 The adsorption-desorption curve of the multi-level pore MnFe2O4 catalyst obtained in Example 1;

[0033] Figure 3 This is the pore size distribution diagram of the multi-level pore MnFe2O4 catalyst obtained in Example 1;

[0034] Figure 4 This is a diagram showing the stability effect of the multi-level pore MnFe2O4 catalyst obtained in Example 1. DETAILED DESCRIPTION

[0035] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0036] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0037] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0038] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.

[0039] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0040] Example 1

[0041] Weigh 10.2g of citric acid monohydrate, 5.3g of ferric acetate and 2.0g of manganese nitrate. Grind and mix the three raw materials in a mortar for 20 minutes until they are uniformly mixed. Finally, transfer the uniformly mixed mixture to a muffle furnace, heat it to 500°C at a heating rate of 2°C / min, and keep it at this temperature for 3h to obtain a black product, which is a multi-level porous MnFe2O4 catalyst.

[0042] The scanning electron microscopy (SEM) results of the multi-level porous MnFe2O4 catalyst prepared in this example are as follows: Figure 1 As shown by Figure 1 It can be seen that the multi-level porous MnFe2O4 catalyst contains multi-level pores such as micropores, mesopores, and macropores, and has a sponge-like pore structure.

[0043] The adsorption-desorption curve of the multi-level porous MnFe2O4 catalyst prepared in this example is shown in Figure 2 As shown, the pore size distribution diagram of the multi-level porous MnFe2O4 catalyst prepared in this embodiment is as follows Figure 3 As shown by Figure 2 and Figure 3 It can be seen that the present invention successfully synthesized a multi-level porous MnFe2O4 catalyst with a specific surface area of ​​215.9 m 2 / g.

[0044] The method and effect of catalytic degradation of methyl mercaptan by the multi-level porous MnFe2O4 catalyst obtained in this embodiment are as follows:

[0045] The prepared multi-level porous MnFe2O4 catalyst was sieved to 40-60 mesh and loaded into the reactor. The loading mass of the multi-level porous MnFe2O4 catalyst was 0.04 g. The methyl mercaptan concentration was 100 ppm and the total space velocity was set to 100,000 h -1 The reaction system pressure was normal pressure, and the reaction temperature was set at 30° C. to conduct a catalytic degradation evaluation experiment of methyl mercaptan. The experimental results showed that the degradation rate of methyl mercaptan could reach 100% at 30° C.

[0046] The test method and results of the stability of the multi-level porous MnFe2O4 catalyst for catalytic degradation of methyl mercaptan in this example are as follows:

[0047] The prepared multi-level porous MnFe2O4 catalyst was sieved to 40-60 mesh and loaded into the reactor. The loading mass of the multi-level porous MnFe2O4 catalyst was 0.2 g. The methyl mercaptan concentration was 500 ppm and the total space velocity was set to 100,000 h -1 The reaction system pressure was normal pressure, the reaction temperature was set at 30°C, and the stability evaluation experiment of methyl mercaptan catalytic degradation was carried out. The experimental results showed that when the degradation temperature was 30°C and the methyl mercaptan degradation rate was 99%, the stability could reach 407h, and the methyl mercaptan degradation rate was 100% when the time was ≤400h (see Figure 4 ).

[0048] The regeneration of the multi-level porous MnFe2O4 catalyst obtained in this example was tested, and the test method and results are as follows:

[0049] Detection method: The prepared multi-level porous MnFe2O4 catalyst was loaded into a fixed bed reactor, and 100 ppm methyl mercaptan gas was introduced, and the space velocity was set to 100,000 h -1 , the reaction temperature is 30°C, and the reaction pressure is normal pressure. The catalyst is operated continuously for 60 hours under the above conditions, and the degradation rate of methyl mercaptan is recorded, which is recorded as the initial degradation rate of methyl mercaptan. After the reaction is completed, the catalyst is taken out and washed with deionized water for 2 hours. Then, the washed catalyst is dried at 100°C for 2 hours. The dried catalyst is reloaded into the reactor, and the above reaction conditions are repeated to test the regeneration performance. In order to comprehensively evaluate the regeneration performance of the catalyst, the above use and recovery steps are repeated for 3 cycles. The degradation rate of methyl mercaptan is recorded after each cycle to evaluate the regeneration performance of the catalyst.

[0050] Test results: the degradation rate of methyl mercaptan was 100% at the beginning; the degradation rate of methyl mercaptan after the first regeneration was 92%; the degradation rate of methyl mercaptan after the second regeneration was 90%; the degradation rate of methyl mercaptan after the third regeneration was 85%. After multiple regenerations, the degradation rate of methyl mercaptan by the catalyst can still reach more than 85%, indicating that the multi-level porous MnFe2O4 catalyst obtained by the present invention has good regeneration performance.

[0051] Example 2

[0052] Weigh 14.7g of citric acid monohydrate, 3.4g of ferric nitrate and 2.5g of manganese nitrate. Grind and mix the three raw materials in a mortar for 30 minutes until they are uniformly mixed. Finally, transfer the uniformly mixed mixture to a muffle furnace, heat it to 450℃ at a heating rate of 2℃ / min, and keep it at this temperature for 3h to obtain a black product, which is a multi-level porous MnFe2O4 catalyst.

[0053] The method and effect of catalytic degradation of methyl mercaptan by the multi-level porous MnFe2O4 catalyst obtained in this embodiment are as follows:

[0054] The prepared multi-level porous MnFe2O4 catalyst was sieved to 40-60 mesh and loaded into the reactor. The loading mass of the multi-level porous MnFe2O4 catalyst was 0.04 g. The methyl mercaptan concentration was 1000 ppm and the total space velocity was set to 100000 h -1 The reaction system pressure was normal pressure, and the reaction temperature was set at 30° C. to conduct a catalytic degradation evaluation experiment of methyl mercaptan. The experimental results showed that the degradation rate of methyl mercaptan was 100% at 30° C.

[0055] The test method and results of the stability of the multi-level porous MnFe2O4 catalyst for catalytic degradation of methyl mercaptan in this example are as follows:

[0056] The prepared multi-level porous MnFe2O4 catalyst was sieved to 40-60 mesh and loaded into the reactor. The loading mass of the multi-level porous MnFe2O4 catalyst was 0.2 g. The methyl mercaptan concentration was 1000 ppm and the total space velocity was set to 100000 h -1 The reaction system pressure was normal pressure, the reaction temperature was set at 30°C, and the stability evaluation experiment of methyl mercaptan catalytic degradation was carried out. The experimental results showed that when the degradation temperature was 30°C and the methyl mercaptan degradation rate was 100%, the stability was 102h.

[0057] Example 3

[0058] Weigh 8.1g of citric acid monohydrate, 2.7g of ferric nitrate and 2g of manganese nitrate. Grind and mix the three raw materials in a mortar for 50min until they are uniformly mixed. Finally, transfer the uniformly mixed mixture to a muffle furnace, heat it to 500℃ at a heating rate of 2℃ / min, and keep it at this temperature for 2h to obtain a black product, which is a multi-level porous MnFe2O4 catalyst.

[0059] The method and effect of catalytic degradation of methyl mercaptan by the multi-level porous MnFe2O4 catalyst obtained in this embodiment are as follows:

[0060] The prepared multi-level porous MnFe2O4 catalyst was sieved to 40-60 mesh and loaded into the reactor. The loading mass of the multi-level porous MnFe2O4 catalyst was 0.04 g. The methyl mercaptan concentration was 100 ppm and the total space velocity was set to 200,000 h -1 The reaction system pressure was normal pressure, and the reaction temperature was set at 30° C. to conduct a catalytic degradation evaluation experiment of methyl mercaptan. The experimental results showed that the degradation rate of methyl mercaptan was 100% at 30° C.

[0061] The test method and results of the stability of the multi-level porous MnFe2O4 catalyst for catalytic degradation of methyl mercaptan in this example are as follows:

[0062] The prepared multi-level porous MnFe2O4 catalyst was sieved to 40-60 mesh and loaded into the reactor. The loading mass of the multi-level porous MnFe2O4 catalyst was 0.2 g. The methyl mercaptan concentration was 100 ppm and the total space velocity was set to 200,000 h -1 The reaction system pressure was normal pressure, the reaction temperature was set at 30°C, and the stability evaluation experiment of methyl mercaptan catalytic degradation was carried out. The experimental results showed that when the degradation temperature was 30°C and the methyl mercaptan degradation rate was 100%, the stability could reach 65h.

[0063] Comparative Example 1

[0064] The difference from Example 1 is that the addition of citric acid monohydrate is omitted; the rest is the same as Example 1.

[0065] The method and effect of catalytic degradation of methyl mercaptan by the catalyst obtained in this comparative example are as follows:

[0066] The prepared catalyst was sieved to 40-60 mesh and loaded into the reactor. The loading mass of the catalyst was 0.04 g. The concentration of methyl mercaptan was 100 ppm and the total space velocity was set to 100,000 h -1 The reaction system pressure was normal pressure, and the reaction temperature was set at 30° C. to conduct a catalytic degradation evaluation experiment of methyl mercaptan. The experimental results showed that the degradation rate of methyl mercaptan could reach 100% at 30° C.

[0067] The test method and results of the stability of the catalyst obtained in this comparative example in catalytic degradation of methyl mercaptan are as follows:

[0068] The prepared catalyst was sieved to 40-60 mesh and loaded into the reactor. The loading mass of the catalyst was 0.2 g. The concentration of methyl mercaptan was 500 ppm and the total space velocity was set to 100,000 h -1 The reaction system pressure was normal pressure, the reaction temperature was set at 30°C, and the stability evaluation experiment of methyl mercaptan catalytic degradation was carried out. The experimental results showed that when the degradation temperature was 30°C and the methyl mercaptan degradation rate was 90%, the stability could reach 13h.

[0069] Comparative Example 2

[0070] The difference from Example 1 is that the addition of manganese nitrate is omitted; the rest is the same as Example 1.

[0071] The method and effect of catalytic degradation of methyl mercaptan by the catalyst obtained in this comparative example are as follows:

[0072] The prepared catalyst was sieved to 40-60 mesh and loaded into the reactor. The loading mass of the catalyst was 0.04 g. The concentration of methyl mercaptan was 100 ppm and the total space velocity was set to 100,000 h -1 The reaction system pressure was normal pressure, and the reaction temperature was set at 30° C. to conduct a catalytic degradation evaluation experiment of methyl mercaptan. The experimental results showed that the degradation rate of methyl mercaptan could reach 100% at 30° C.

[0073] The test method and results of the stability of the catalyst obtained in this comparative example in catalytic degradation of methyl mercaptan are as follows:

[0074] The prepared catalyst was sieved to 40-60 mesh and loaded into the reactor. The loading mass of the catalyst was 0.2 g. The concentration of methyl mercaptan was 500 ppm and the total space velocity was set to 100,000 h -1 The reaction system pressure was normal pressure, the reaction temperature was set at 30°C, and the stability evaluation experiment of methyl mercaptan catalytic degradation was carried out. The experimental results showed that when the degradation temperature was 30°C and the methyl mercaptan degradation rate was 90%, the stability could reach 13h.

[0075] Comparative Example 3

[0076] The difference from Example 1 is that the addition of ferric acetate is omitted; the rest is the same as Example 1.

[0077] The method and effect of catalytic degradation of methyl mercaptan by the catalyst obtained in this comparative example are as follows:

[0078] The prepared catalyst was sieved to 40-60 mesh and loaded into the reactor. The loading mass of the catalyst was 0.04 g. The concentration of methyl mercaptan was 100 ppm and the total space velocity was set to 100,000 h -1 The reaction system pressure was normal pressure, and the reaction temperature was set at 30° C. to conduct a catalytic degradation evaluation experiment of methyl mercaptan. The experimental results showed that the degradation rate of methyl mercaptan could reach 100% at 30° C.

[0079] The test method and results of the stability of the catalyst obtained in this comparative example in catalytic degradation of methyl mercaptan are as follows:

[0080] The prepared catalyst was sieved to 40-60 mesh and loaded into the reactor. The loading mass of the catalyst was 0.2 g. The concentration of methyl mercaptan was 500 ppm and the total space velocity was set to 100,000 h -1The reaction system pressure was normal pressure, the reaction temperature was set at 30°C, and the stability evaluation experiment of methyl mercaptan catalytic degradation was carried out. The experimental results showed that when the degradation temperature was 30°C and the methyl mercaptan degradation rate was 90%, the stability could reach 19h.

[0081] Comparative Example 4

[0082] The difference from Example 1 is that the amount of manganese nitrate is increased to ensure that the molar ratio of ferric acetate to manganese nitrate is 1:1.16; the rest is the same as Example 1.

[0083] The method and effect of catalytic degradation of methyl mercaptan by MnFe2O4 catalyst obtained in this comparative example are as follows:

[0084] The prepared MnFe2O4 catalyst was sieved to 40-60 mesh and loaded into the reactor. The loading mass of MnFe2O4 catalyst was 0.04 g. The concentration of methyl mercaptan was 100 ppm and the total space velocity was set to 100,000 h -1 The reaction system pressure was normal pressure, and the reaction temperature was set at 30° C. to conduct a catalytic degradation evaluation experiment of methyl mercaptan. The experimental results showed that the degradation rate of methyl mercaptan could reach 100% at 30° C.

[0085] The test method and results of the stability of the MnFe2O4 catalyst for catalytic degradation of methyl mercaptan obtained in this comparative example are as follows:

[0086] The prepared MnFe2O4 catalyst was sieved to 40-60 mesh and loaded into the reactor. The loading mass of MnFe2O4 catalyst was 0.2 g. The concentration of methyl mercaptan was 500 ppm and the total space velocity was set to 100,000 h -1 The reaction system pressure was normal pressure, the reaction temperature was set at 30°C, and the stability evaluation experiment of methyl mercaptan catalytic degradation was carried out. The experimental results showed that when the degradation temperature was 30°C and the methyl mercaptan degradation rate was 100%, the stability could reach 32h.

[0087] Comparative Example 5

[0088] The difference from Example 1 is that the calcination temperature is 800° C.; the rest is the same as Example 1.

[0089] The method and effect of catalytic degradation of methyl mercaptan by the catalyst obtained in this comparative example are as follows:

[0090] The prepared multi-level porous MnFe2O4 catalyst was sieved to 40-60 mesh and loaded into the reactor. The loading mass of the multi-level porous MnFe2O4 catalyst was 0.04 g. The methyl mercaptan concentration was 100 ppm and the total space velocity was set to 100,000 h -1The reaction system pressure was normal pressure, and the reaction temperature was set at 30° C. to conduct a catalytic degradation evaluation experiment of methyl mercaptan. The experimental results showed that the degradation rate of methyl mercaptan was 100% at 30° C.

[0091] The test method and results of the stability of the catalyst obtained in this comparative example in catalytic degradation of methyl mercaptan are as follows:

[0092] The prepared multi-level porous MnFe2O4 catalyst was sieved to 40-60 mesh and loaded into the reactor. The loading mass of the multi-level porous MnFe2O4 catalyst was 0.2 g. The methyl mercaptan concentration was 500 ppm and the total space velocity was set to 100,000 h -1 The reaction system pressure was normal pressure, the reaction temperature was set at 30°C, and the stability evaluation experiment of methyl mercaptan catalytic degradation was carried out. The experimental results showed that when the degradation temperature was 30°C and the methyl mercaptan degradation rate was 100%, the stability was 6h.

[0093] Comparative Example 6

[0094] The difference from Example 1 is that the calcination temperature is 250° C. and the calcination time is 2 h; the rest is the same as Example 1.

[0095] The method and effect of catalytic degradation of methyl mercaptan by the catalyst obtained in this comparative example are as follows:

[0096] The prepared multi-level porous MnFe2O4 catalyst was sieved to 40-60 mesh and loaded into the reactor. The loading mass of the multi-level porous MnFe2O4 catalyst was 0.04 g. The methyl mercaptan concentration was 100 ppm and the total space velocity was set to 100,000 h -1 The reaction system pressure was normal pressure, and the reaction temperature was set at 30° C. to conduct a catalytic degradation evaluation experiment of methyl mercaptan. The experimental results showed that the degradation rate of methyl mercaptan was 93% at 30° C.

[0097] The test method and results of the stability of the catalyst obtained in this comparative example in catalytic degradation of methyl mercaptan are as follows:

[0098] The prepared multi-level porous MnFe2O4 catalyst was sieved to 40-60 mesh and loaded into the reactor. The loading mass of the multi-level porous MnFe2O4 catalyst was 0.2 g. The methyl mercaptan concentration was 500 ppm and the total space velocity was set to 100,000 h -1 The reaction system pressure was normal pressure, the reaction temperature was set at 30°C, and the stability evaluation experiment of methyl mercaptan catalytic degradation was carried out. The experimental results showed that when the degradation temperature was 30°C and the methyl mercaptan degradation rate was higher than 90%, the stability was 3.5h.

[0099] The various embodiments in this specification are described in a progressive manner, and each embodiment focuses on the differences from other embodiments. The same or similar parts between the various embodiments can be referenced to each other.

[0100] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A method for preparing a multi-level porous MnFe2O4 catalyst for catalytic degradation of methyl mercaptan at room temperature, characterized in that: The steps include: The iron source, the manganese source and the template are ground and mixed to obtain a mixture; the mixture is calcined to obtain the multi-level porous MnFe2O4 catalyst.

2. The method for preparing the multi-level porous MnFe2O4 catalyst for catalytic degradation of methyl mercaptan at room temperature according to claim 1, characterized in that: The iron source includes one or more of ferric nitrate, ferric chloride and ferric acetate; the manganese source includes one or more of manganese nitrate, manganese chloride, manganese acetate and potassium permanganate.

3. The method for preparing the multi-level porous MnFe2O4 catalyst for catalytic degradation of methyl mercaptan at room temperature according to claim 1, characterized in that: The template agent includes citric acid and / or oxalic acid.

4. The method for preparing the multi-level porous MnFe2O4 catalyst for catalytic degradation of methyl mercaptan at room temperature according to claim 1, characterized in that: The molar ratio of the iron source, the manganese source and the template is 1-3:1:1-10.

5. The method for preparing the multi-level porous MnFe2O4 catalyst for catalytic degradation of methyl mercaptan at room temperature according to claim 1, characterized in that: The grinding and mixing time is 10 to 60 minutes.

6. The method for preparing the multi-level porous MnFe2O4 catalyst for catalytic degradation of methyl mercaptan at room temperature according to claim 1, characterized in that: The calcination is carried out in an air atmosphere, the calcination temperature is 300-500° C., the calcination heating rate is 2-10° C., and the calcination heat preservation time is 2-4 hours.

7. The multi-level porous MnFe2O4 catalyst prepared by the method for preparing the multi-level porous MnFe2O4 catalyst for catalytic degradation of methyl mercaptan at room temperature as claimed in any one of claims 1 to 6.

8. Use of the multi-level porous MnFe2O4 catalyst according to claim 7 in catalytic degradation of methyl mercaptan at room temperature.

9. The method for catalytic degradation of methyl mercaptan using the multi-level porous MnFe2O4 catalyst at room temperature as claimed in claim 7, characterized in that: The steps include: The multi-level porous MnFe2O4 catalyst is loaded into the reactor, and methyl mercaptan is introduced into the reactor to perform catalytic degradation of methyl mercaptan.

10. The method for catalytic degradation of methyl mercaptan using a multi-level porous MnFe2O4 catalyst at room temperature according to claim 9, characterized in that: The particle size of the multi-level porous MnFe2O4 catalyst is 40-60 meshes, and the loading amount of the multi-level porous MnFe2O4 catalyst is 0.04-0.2g; the concentration of the methyl mercaptan is 1-5000ppm, and the space velocity of the methyl mercaptan is 10-200000h -1 ; The pressure of the catalytic degradation is normal pressure, and the temperature of the catalytic degradation is normal temperature.

Citation Information

Patent Citations

  • In-situ hybridization room-temperature formaldehyde removal catalyst, preparation method and applications thereof, and composite gel, preparation method and applications thereof

    CN110639542A

  • Preparation and application of foamed spinel type catalyst

    CN115920889A

  • Deodorizing catalyst and production therefor

    JP1995100382A